Pedagogical Pathways for Indigenous Business Education: Learning from Current Indigenous Business Practices - Berge, Simon T. (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
Business is one of the fastest growing areas in post-secondary education, but there is little understanding of Indigenous business practices. This article looks at three Arctic communities in the Yukon, the Northwest Territories, and Nunavut, and their associated co-operative businesses. I examine how these businesses express cultural values, as well as the business skill needs within these communities. Key informant interviews were conducted in each of the three Arctic communities, and three conclusions were made: (a) Co-operatives act as links between communities and their economic activities, (b) Business skills within communities need to be developed, and (c) Business skills need to include cultural components, as co-ops represent cultural economic expressions.